OP80 Effectiveness of european fans in training (EuroFIT): randomised controlled trial in england, portugal, the netherlands and norway. (September 2018) - Wyke, S; Bunn, C; Andersen, E; Gill, J; Gray, CM; Hunt, K; McConnachie, A; van Nassau, F; Silva, MN; van der Ploeg, HP
Abstract : Background: Despite widespread knowledge about the risks of unhealthy lifestyles, men can be reluctant to engage in lifestyle change programmes. Building on the success of the Scottish Football Fans in Training, we developed EuroFIT, a men-only, group-based lifestyle-change program to improve physical activity and reduce sitting time. Our aim was to investigate whether EuroFIT can help men aged 30–65 years with a self-reported BMI ≥27 kg/m 2 to increase physical activity and decrease sitting time 12 months after baseline. Methods: We conducted a pragmatic, two-arm, randomised controlled trial in 15 football clubs in the Netherlands, Norway, Portugal and the UK (England). We measured participants at baseline, post-program and 12 months after baseline. Primary outcomes were objectively assessed changes in total physical activity (steps per day) and total sedentary time (minutes per day spent sitting). Secondary outcomes include self-reported food intake, weight, resting systolic and diastolic blood pressure and cardio-metabolic blood biomarkers. We conducted linear mixed effects regression analyses, including random effects for country and football club, and fixed effects for study group and baseline measurement. Results: 560 men were allocated to the intervention and objective measurements were achieved for 451 (81%) at 12 months; 553 were allocated to the control and objective measurements were achieved for 470 (83%). At 12 months, the mean difference in step count, adjusted for baseline steps and club, was 678 steps (308, 1048) in favour of the intervention (p<0.001); the mean difference in time spent sitting was 1.7 min (−10.4, 13.8) (p=0.78). We also found significicant improvements in self-reported food intake, weight, resting blood pressure and some cardio-metabolic blood biomakers in favour of the intervention. Seven serious adverse events were reported. Of these, 5 were assessed as likely to be associated with EuroFIT participation. Discussion: Participation in EuroFIT led to modest improvement in physical activity but not sedentary time at 12 months. Public health messages to be more physically active and eat well are now widely understood but the 'sit less' message is newer and less is known about how to achieve it. In this context coaches and participants may have found it difficult to disentangle advice about sitting less from advice about being more physical activity. Differences in outcomes between FFIT and EuroFIT will be discussed. Authorship is on behalf of the EuroFIT consortium.